2014
DOI: 10.1155/2014/157137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MWCNT on Thermal, Mechanical, and Morphological Properties of Polybutylene Terephthalate/Polycarbonate Blends

Abstract: This paper evaluated the effect of multiwall carbon nanotube (MWCNT) on the properties of PBT/PC blends. The nanocomposites were obtained by melt blending MWCNT in the weight percentages 0.15, 0.3, and 0.45 wt% with PBT/PC blends in a high performance corotating twin screw extruder. Samples were characterized by tensile testing, dynamic mechanical analysis, thermal analysis, scanning electron microscopy, and X-ray diffraction. Concentrations of PBT and PC are optimized as 80 : 20 based on mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…The ability of MWCNT to improve properties of different polymer blend systems is known . Rejisha et al reported the improved mechanical, thermal, and morphological properties of polybutylene terephthalate/polycarbonate blends with the incorporation of MWCNTs . Arif et al reported the influence of MWCNT in the crystallisation rate of polycarbonate/polypropylene blend .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of MWCNT to improve properties of different polymer blend systems is known . Rejisha et al reported the improved mechanical, thermal, and morphological properties of polybutylene terephthalate/polycarbonate blends with the incorporation of MWCNTs . Arif et al reported the influence of MWCNT in the crystallisation rate of polycarbonate/polypropylene blend .…”
Section: Introductionmentioning
confidence: 99%
“…The increase in tensile strength suggests that the load transfer from PC to MWCNT is improved by the use of f‐MWCNTs. Rejisha et al studied the effect of MWCNTs on the mechanical properties of polybutylene terephthalate (PBT)/PC blends (Table ). The ultimate tensile strength of the nanocomposites was increased from 54 to 85 MPa with addition of MWCNT up to 0.3% in PBT/PC blend (80/20).…”
Section: Pc/cnt Nanocompositesmentioning
confidence: 99%
“…Recent improvement in electrical properties of PC/CNT composites is discussed in the present review paper, and some significant data from those studies are presented in Table . The studies on electrical properties of PC/CNT nanocomposites show that EC of these nanocomposites follows the classical percolating behavior with percolation threshold varying between 1 to 5 wt% . Interestingly, because of the high aspect ratio and small diameter of CNTs, the values of percolation threshold of CNT‐based nanocomposites are much less compared with carbon black and CF‐based nanocomposites whose percolation thresholds are usually up to 15 to 20 wt% and 9 to 18 wt%, respectively …”
Section: Pc/cnt Nanocompositesmentioning
confidence: 99%
“…Among carbon‐based nanomaterials, the remarkable properties of CNTs turned the attention of researchers for its diversified applications and proved to be exciting nanofiller for polymeric composites, energy‐storage devices, sensors, biomedical applications, and so forth. However, the commercial use CNTs in structural applications were limited due to their agglomeration tendency, high cost of production and some unresolved issues regarding the synthesis of high‐quality nanotubes …”
Section: Introductionmentioning
confidence: 99%